FITOTOXICIDADE DE HERBICIDAS PÓS-EMERGENTES SELETIVOS A MILHO (ZEA MAYS L.) EM MUDAS DE AMENDOIM FORRAGEIRO (ARACHIS PINTOI CV. ALQUEIRE) - Andreazza, Tiago; Maixner, Adriano R.; Coppetti, Felipe E.; Coppetti, Daniel E.; Vivian, Rafael; Sartori, Cesar O. (Salão do Conhecimento, 2013)
Resumo